2012
DOI: 10.1037/a0028073
|View full text |Cite
|
Sign up to set email alerts
|

Memory indexing: A novel method for tracing memory processes in complex cognitive tasks.

Abstract: We validate an eye-tracking method applicable for studying memory processes in complex cognitive tasks. The method is tested with a task on probabilistic inferences from memory. It provides valuable data on the time course of processing, thus clarifying previous results on heuristic probabilistic inference. Participants learned cue values of decision alternatives that were arranged within spatial frames. Later, they were told about the validities of cue dimensions and performed memory-based binary choice tasks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
43
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 41 publications
9
43
1
Order By: Relevance
“…This phenomenon in which individuals, while retrieving information from memory, gaze back at spatial locations previously associated with that information (during encoding) has been observed by other studies across different contexts and domains (Johansson & Johansson, 2014;Platzer, Bröder, & Heck, 2014;Renkewitz & Jahn, 2012;Scholz, Mehlhorn, & Krems, 2016;Scholz, von Helversen, & Rieskamp, 2015;Spivey & Geng, 2001). Collectively, these studies suggest that eye movements can be used as a measure of memory retrieval without the need for self-report responses.…”
Section: Eye-movement Measures Of Memory Retrievalsupporting
confidence: 74%
“…This phenomenon in which individuals, while retrieving information from memory, gaze back at spatial locations previously associated with that information (during encoding) has been observed by other studies across different contexts and domains (Johansson & Johansson, 2014;Platzer, Bröder, & Heck, 2014;Renkewitz & Jahn, 2012;Scholz, Mehlhorn, & Krems, 2016;Scholz, von Helversen, & Rieskamp, 2015;Spivey & Geng, 2001). Collectively, these studies suggest that eye movements can be used as a measure of memory retrieval without the need for self-report responses.…”
Section: Eye-movement Measures Of Memory Retrievalsupporting
confidence: 74%
“…Because process tracing has usually been performed on novel stimuli, we do not know enough about how memory processes affect visual attention in decision making (cf. Renkewitz & Jahn, 2012).…”
Section: Memory and Visually Available Informationmentioning
confidence: 99%
“…For instance, participants who first encode an arrangement of objects and are later asked to recall aspects of that arrangement while looking at a blank screen will spontaneously execute eye movements "to nothing" on the blank screen, which largely correspond to the original object arrangement (e.g., Altman, 2004;Johansson & Johansson, 2014;Spivey & Geng, 2001). Research using such a blank-screen design has demonstrated that eye-movement patterns typical of various decision making strategies remain when decisionrelevant information is removed from the display and the decision is made strictly from memory (Jahn & Braatz, 2014;Renkewitz & Jahn, 2012;Scholz, von Helversen, & Rieskamp, 2015). In addition, compatibility of gaze positions between encoding and retrieval can increase the likelihood of successful remembering (Johansson & Johansson, 2014) and may trigger other associated memories (Platzer, Bröder, & Heck, 2014).…”
Section: Memory and Visually Available Informationmentioning
confidence: 99%
“…By using the location as a retrieval cue, looking at nothing facilitates memory retrieval for information associated with this location (Ferreira, Apel, & Henderson, 2008). Using a decision task, Renkewitz and Jahn (2012) provided evidence that gaze behavior can validly indicate which piece of information people try to retrieve.…”
Section: Spatial Cueing Of Verbal Cue Informationmentioning
confidence: 99%